3HP preventive treatment among children and adolescents with HIV and child household contacts of TB patients - A. Kinikar; R. Borse; B. Randive; P. Kamath; S.K. Mattoo; M. Parmar; H. Solanki; V. Mave; A. Gupta; R.E. Chaisson; N. Suryavanshi (IJTLD Open)
INTRODUCTION: India’s National TB Elimination Programme plans to roll out short-course TB preventive therapy (TPT) using 3 months of rifapentine and isoniazid (3HP). Understanding the feasibility and safety of children in programmatic settings is critical for widespread implementation. We present the findings of a targeted scale-up of 3HP among children and adolescents living with HIV (CALHIV) and child household contacts (>2 to <6 years) of pulmonary TB patients (CHHC). METHODS: Between December 2021 and July 2023, eligible CALHIV and CHHC participants were given weekly dosages of 3HP for 3 months at antiretroviral therapy (ART) and TB clinics, respectively, of a public hospital in Pune, India. RESULTS: Of 97 children screened, 91 initiated 3HP (32 CALHIV and 59 CHHC). The median age of CALHIV was 14 years; 66% were male and on dolutegravir-based ART. The median age of CHHC was 4 years; 47% were males. Thirty-one (97%) CALHIV and 56 (95%) CHHC completed 3HP without dolutegravir dose adjustment. None of the child participants discontinued 3HP due to adverse events. No child participant developed TB during 1 year of follow-up post-3HP. CONCLUSION: Our study provides evidence of the uptake and feasibility of the planned nationwide rollout of 3HP.